Frontiers in Nano-therapeutics - Tasnim, Nishat; Nair, Baiju G.; Sai Krishna, Katla; Kalagara, Sudhakar; Narayan, Mahesh; Noveron, Juan C.; Joddar, Binata; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This brief highlights recent research advances in the area of nano-therapeutics. Nanotechnology holds immense potential for application in a wide range of biological and engineering applications such as molecular sensors for disease diagnosis, therapeutic agents for the treatment of diseases, a vehicle for delivering therapeutics and imaging agents for theranostic applications, both in-vitro and in-vivo. The brief is grouped into the following sections namely, A) Discrete Nanosystems ; B) Anisotropic Nanoparticles; C) Nano-films/coated/layered and D) Nano-composites.
Introduction -- Anisotropic Nanoparticles -- Supra-nano particles -- Nano-layered particles -- Discreet nano-systems -- Nanocomposites -- Conclusions.
Keywords: Biomedical engineering; Microtechnology; Microelectromechanical systems; Biomaterials; Medicine -- Research; Biology -- Research; Clinical biochemistry; Medical physics; Biomedical Engineering and Bioengineering; Microsystems and MEMS; Biomaterials; Biomedical Research; Medical Biochemistry; Medical Physics